Tissue doppler imaging in thalassemia major patients: correlation between systolic and diastolic function with serum ferritin level - Syarif Rohimi; Najib Advani; Sudigdo Sastroasmoro; Bambang Mardiyono; Sukman Tulus Putra; Mulyadi M. Djer; Fajar Subroto (Paediatrica Indonesiana, 2012)
Background Thalassemia is a major public health problem inIndonesia. Cardiac diseases remain as the main cause of death inthese patients due to iron overload. Although the T2* magneticresonance imaging has been considered as the gold standard forassessing cardiac iron overload but it has limited availability.The tissue doppler imaging (TDI) echocardiography, a fairly newand easy method that is suggested, can detect early abnormalmyocardial iron overload.Objective To assess myocardial systolic and diastolic functionof thalassemic patients using TDI and examine their correlationwith serum ferritin level.Methods A crossô€Œsectional study was conducted from January toMarch 2011 at the Harapan Kita Women and Children Hospital.We performed clinical examination, serum ferritin level, as wellas conventional and tissue doppler echocardiography on allsubjects.Results We included 34 regularlyô€Œtranfused patients, of which17 were boys. The mean age of the subjects was 11.6 (SD 4.7years, range 2.6 ô€Œ 20 years). Mean pulse rate and blood pressurewere within normal range. Hemoglobin level at inclusion rangedfrom 5.8 to 6 g/dL. Almost all patients did not receive regularchelation therapy. Median serum ferritin level was 6275 ng/mL(range 2151 - 17,646 ng/mL). Conventional echocardiographyshowed normal systolic function, but some diastolic dysfunctionswere found including E wave abnormalites in 4 patients, A waveabnormalites in 3, and E/A ratio abnormalites found in 3. TheTDI showed decreased systolic function (Sa wave abnormality) in9 patients and diastolic dysfunctions (Ea wave abnormality in 11patients and Aa wave abnormaly in 2). No abnormality was foundin Ea/Aa and ElEa ratios. There was a weak negative correlationbetween ferritin level and Sa wave and Ea wave respectively anda moderately negative correlation between ferritin level and Ea/Aa ratio. There was no correlation between serum ferritin andAa wave or ElEa ratio.Conclusion TDI identifies a greater number of patients Mthsystolic and diastolic myocardial dysfunction than was revealedby conventional echocardiography. There was a weak negativecorrelation between serum ferritin to Sa wave and Ea wave, and amoderately negative correlation between ferritin and Ea/Aa ratio.There was no correlation between serum ferritin and Aa wave orElEa ratio. [paediatr Indones. 2012;52:187,93].